Mechanism of histone deacetylases in cardiac hypertrophy and its therapeutic inhibitors - Han, Yu; Nie, Jiali; Wang, Dao Wen; Ni, Li (Frontiers in Cardiovascular Medicine, 2022)
Cardiac hypertrophy is a key process in cardiac remodeling development, leading to ventricle enlargement and heart failure. Recently, studies show the complicated relation between cardiac hypertrophy and epigenetic modification. Post-translational modification of histone is an essential part of epigenetic modification, which is relevant to multiple cardiac diseases, especially in cardiac hypertrophy. There is a group of enzymes related in the balance of histone acetylation/deacetylation, which is defined as histone acetyltransferase (HAT) and histone deacetylase (HDAC). In this review, we introduce an important enzyme family HDAC, a key regulator in histone deacetylation. In cardiac hypertrophy HDAC I downregulates the anti-hypertrophy gene expression, including Kruppel-like factor 4 (Klf4) and inositol-5 phosphatase f (Inpp5f), and promote the development of cardiac hypertrophy. On the contrary, HDAC II binds to myocyte-specific enhancer factor 2 (MEF2)，inhibit the assemble ability to HAT and protect against cardiac hypertrophy. Under adverse stimuli such as pressure overload and calcineurin stimulation, the HDAC II transfer to cytoplasm, and MEF2 can bind to nuclear factor of activated T cells (NFAT) or GATA binding protein 4(GATA4), mediating inappropriate gene expression. HDAC III, also known as SIRTs, can interact not only to transcription factors, but also exist interaction mechanisms to other HDACs, such as HDAC IIa. We also present the latest progress of HDAC inhibitors (HDACi), as a potential treatment target in cardiac hypertrophy.